An analytical model to predict the compressive damage of concrete plates under contact detonation. (December 2019) - Tu, Huan; Fung, Tat Ching; Tan, Kang Hai; Riedel, Werner
Highlights: Quantify shock transmission from explosive to concrete under contact detonation. Analyse blast wave propagation and attenuation in concrete plates. Predict crater damage sizes on concrete plates induced by contact detonation. Abstract: Explosions threaten the safety of buildings and occupants by inducing severe damage to concrete structural elements. The effects of close-in and contact loading situations on RC plates have been investigated in literature and the common approaches employ field test results condensed in engineering charts based on cube-root scaling. In this paper, a new analytical model based on a physical framework is developed to (a) investigate shock wave attenuation along the depth of the concrete plate and (b) predict the size of crater damage. The analytical model for shock wave pressure is discussed in comparison to prediction data from established numerical models and existing experimental results. Moreover, consistency of the newly proposed model with established scaling rules is verified with respect to crater size.